(Meta)genomics -assisted screening of novel antibacterial lactic acid bacteria strains from traditional fermented milk from Western China and their bioprotective effects on cheese. (1st February 2023) - Li, Lin; Zhang, Linxuan; Zhang, Tingting; Liu, Yuanfa; Lü, Xin; Kuipers, Oscar P.; Yi, Yanglei
Abstract: In this study, the bacterial composition of five traditional fermented milk samples from western China was evaluated by 16S metagenomic analysis. Forty lactic acid bacteria (LAB) strains were isolated from each sample and their antilisterial activity was tested. The inter-strain genetic diversity of the LAB isolated was investigated by randomly amplified polymorphic DNA (RAPD) analysis with reference to their antilisterial activity. The antimicrobial potential of selected LAB strains was studied by whole genome sequencing and mining, which resulted in the identification of several novel biosynthetic gene clusters (BGCs). Lactiplantibacillus plantarum TXZ2-35, Limosilactobacillus fermentum TZ-22 and Companilactobacillus crustorum QHS-4, carrying novel BGCs, were used as bio-protective adjunct cultures in Cheddar cheese. These three strains were able to control the proliferation of Listeria monocytogenes in cheese and some strains could improve cheese quality in terms of texture and sensory quality. In summary, we applied metagenomic and genomic approaches to quickly identify novel antilisterial LAB strains from traditional fermented food. Our results demonstrate the effectiveness of incorporating novel bioprotective adjunct cultures in improving the safety and quality of cheese. Highlights: Rapid screening of novel bioprotective strains guided by (meta)genomics. Geographical location and the draining process affect microbial composition of fermented milk. Random amplified polymorphism reveals strain-dependent variation. Lactobacillus has great potential as bioprotective adjunct culture for cheese.